MMP9-Associated Tumor Stem Cells, CCL1-Silenced Dendritic Cells, and Cytokine-Induced Killer Cells Have a Remarkable Therapeutic Efficacy for Acute Myeloid Leukemia by Activating T Cells - Min Dong; Guozhen Zhang; Jie Meng; Biou Liu; Duanfeng Jiang; Feng Liu (Hindawi Limited, 2023)
Purpose. Dendritic cells (DC) are specialized antigen-presenting cells, and cytokine-induced killer (CIK) cells have a specific killing activity to a variety of tumors. However, the underlining mechanism and function of DC-CIK cells in acute myeloid leukemia (AML) remain largely elusive. Methods. Gene expression profiles of leukemia patients were obtained from TCGA, DC cell components were evaluated using the quanTIseq method, and cancer stem cell scores were estimated using machine learning methods. The transcriptomes were obtained in DC-CIK cells from normal and AML patients by high-throughput sequencing. Large differentially expressed mRNAs were verified by RT-qPCR assay, and MMP9 and CCL1 were selected for subsequent studies in vivo and in vitro experiments. Results. Significant positive correlations were found with DC versus cancer stem cells (p=0.008) and the expression of MMP9 versus cancer stem cells (p=0.018). MMP9 and CCL1 were found to be highly expressed in DC-CIK cells from AML patients. DC-CIK cells with MMP9 and CCL1 knockout alone had little effect on leukemia cells, while knockdown of MMP9 and CCL1 in DC-CIK cells increased cytotoxicity, suppressed proliferation, and induced apoptosis of leukemia cells. In addition, we proved that MMP9- and CCL1-silenced DC-CIK cells significantly elevated the CD3+CD4+ and CD3+CD8+ cells and lowered the CD4+PD-1+ and CD8+PD-1+ T cells. Meanwhile, blockage of MMP9 and CCL1 in DC-CIK cells dramatically increased IL-2 and IFN-γ, increased CD107aþ (LAMP-1) and granzyme B (GZMB), and downregulated PD-1, CTLA4, TIM3, and LAG3 T cells from AML patients and AML model mice. Furthermore, activated T cells in DC-CIK cells knocking down MMP9 and CCL1 also prevented proliferation and accelerated apoptosis of AML cells. Conclusion. Our findings demonstrated that blockage of MMP9 and CCL1 in DC-CIK cells could markedly enhance the therapeutic efficiency in AML via activating T cells.